2020
DOI: 10.1051/0004-6361/202039165
|View full text |Cite
|
Sign up to set email alerts
|

A perfect power-law spectrum even at the highest frequencies: The Toothbrush relic

Abstract: Radio relics trace shock fronts generated in the intracluster medium (ICM) during cluster mergers. The particle acceleration mechanism at the shock fronts is not yet completely understood. We observed the Toothbrush relic with the Effelsberg and Sardinia Radio Telescope at 14.25 GHz and 18.6 GHz, respectively. Unlike previously claimed, the integrated spectrum of the relic closely follows a power law over almost three orders of magnitude in frequency, with a spectral index of α58 MHz18.6 GHz = −1.16 ± 0.03. Ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 40 publications
3
31
1
Order By: Relevance
“…Out of about 100 radio halos presently confirmed, three show filaments of polarized emission at around 20% at 1.4 GHz (A2255 Govoni et al 2005, MACS J0717.5+3745 Bonafede et al 2009, andA523 Girardi et al 2016). These are likely projected on the cluster center as suggested by recent studies of A2255 and MACS J0717.5+3745 (Pizzo et al 2011;Botteon et al 2020;Rajpurohit et al 2020). Moreover, a 5𝜎 upper limit of 13% on the fractional polarization has been derived for the radio halo in 1E 0657-55.8 by Shimwell et al (2014).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Out of about 100 radio halos presently confirmed, three show filaments of polarized emission at around 20% at 1.4 GHz (A2255 Govoni et al 2005, MACS J0717.5+3745 Bonafede et al 2009, andA523 Girardi et al 2016). These are likely projected on the cluster center as suggested by recent studies of A2255 and MACS J0717.5+3745 (Pizzo et al 2011;Botteon et al 2020;Rajpurohit et al 2020). Moreover, a 5𝜎 upper limit of 13% on the fractional polarization has been derived for the radio halo in 1E 0657-55.8 by Shimwell et al (2014).…”
mentioning
confidence: 74%
“…Detailed spatially-resolved spectral index images have been produced for a number of radio halos, revealing different behaviours. Indications of radial steepening have been found in a few clusters (e.g., Giovannini et al 1993;Feretti et al 2004;Pearce et al 2017), while other radio halos show no clear trend with either uniform (e.g., Vacca et al 2014;Rajpurohit et al 2018;Hoang et al 2019) or complex (e.g., Giacintucci et al 2005;Orrú et al 2007; Kale & Dwarakanath 2010;Shimwell et al 2014;Rajpurohit et al 2020;Botteon et al 2020) distributions. Radio relics are also characterized by steep-spectra (𝛼 1-1.5), and detailed spectral index images show a steepening transversely to their elongation towards the cluster center (e.g., Clarke & Ensslin 2006;de Gasperin et al 2015;Di Gennaro et al 2018).…”
mentioning
confidence: 99%
“…Recently, it has been found that the integrated spectrum of the Toothbrush (Rajpurohit et al 2020a) and the Sausage relics (Loi et al 2021) both follow a close power-law between 150 MHz to 18.6 GHz and has spectral indices steeper than −1 contrary to previous claims (Stroe et al 2016;Kierdorf et al 2017).…”
Section: Abell 2256mentioning
confidence: 91%
“…Galaxy clusters undergoing mergers often show spectacular, megaparsec-scale radio relics and radio halos (see van Weeren et al 2019, for a recent review). The radio spectra of such sources are steep (α ≤ −1.0 where Di Gennaro et al 2021;Rajpurohit et al 2020aRajpurohit et al , 2021a and believed to originate from shock fronts generated in the intracluster medium (ICM) when galaxy clusters merge (Ensslin et al 1998;Roettiger et al 1999). This connection has been established by finding X-ray surface brightness and temperature discontinuities at the location of some relics (see e.g., Sarazin et al 2013;Ogrean et al 2013;Shimwell et al 2015;van Weeren et al 2016;Botteon et al 2016;Thölken et al 2018;Di Gennaro et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the quasi-stationary shock scenario, as analysed here, a power-law spectra is expected. Nevertheless, Loi et al [26] and Rajpurohit et al [27] produced the most detailed integrated radio spectra for the sausage relic and toothbrush relic, respectively. These observations cover an even larger frequency range, i.e., up to 18.6 GHz.…”
Section: Integrated Radio Spectramentioning
confidence: 99%